Capacity strengthening strategy through capacity needs assessment for country level Strategic Analysis and Knowledge Support System (SAKSS): Ethiopia - Tadesse, Ethiopia; Tsegaye, Wondwossen (International Food Policy Research Institute, 2014)
The capacity needs assessment (CNA) was conducted at three levels: at the policy process/enabling environment level, organizational level, and individual level. The assessment focused on the thematic issues related to (1) strategic policy analysis, (2) M&E, and (3) knowledge management and sharing. Thirteen organizations were covered in this assessment: government ministries, research organizations, universities, and professional associations. In the Ethiopian agriculture policy process, this study noted that the Ethiopian Ministry of Finance and Economic Development (MoFED) has a role in initiating country‐level strategies, while the Ethiopian Ministry of Agriculture (MoA) plays a role in initiating sector‐specific policies such as land policy, seed policy, and others. The Central Statistics Agency (CSA) is the major and the official source of data and information. Research centers and universities, on the other hand, are significant sources of rigorous research and policy analysis reports. The Parliament and the prime minister’s office mainly ratify and follow implementation of policies, while donors play a key role by providing technical expert advice and funds.